Contributions to displacement and resistance of the meniscus-suture complex in transtibial meniscal root repair - Prado-Novoa, María; Pérez-Blanca, Ana; Estébanez-Campos, María Belén; Nadal-Martínez, Fernando; Espejo-Reina, Alejandro; Ceccarelli, Marco (My University, 2019)
This work analyses in a porcine model the contributions of meniscal tissue, suture thread and meniscus-suture interaction to the permanent displacements generated at the repaired root after surgery to re-insert the posterior meniscal root using a transtibial pullout technique. Medial porcine menisci with a single suture applied at the posterior horn were subjected to cyclic and load-to-failure tests. Elongations of the different components of the meniscus-suture complex were determined applying photogrammetry. Results showed that after low intensity cyclic loading, the main contribution to permanent root displacements was due to the thread (51.2%), while no cutting of the suture through tissue occur at the interface. Under load-to-failure conditions, suture cutting started at a significantly higher load level (Suture Retention Strength, SRS), always before and close to the first local maximum of the load-elongation curve, and progressed rapidly afterwards causing the final failure of all specimens
Keywords: Rodillas-Lesiones y heridas-Tratamiento; Biomecánica; Biomechanical properties; Posterior meniscal root; Transtibial pull-out repair; Permanent displacements; Suture Retention Strength